Influence of a normal electric field on surfacewave dynamics - Akimov, Yu.A.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2007)
This paper presents a study of the nonresonant parametric excitation of counter-propagating surface waves by a uniform in space and varying in time electric pump field, perpendicular to a planar plasma-dielectric interface. The criterion of the wave excitation has been derived and analyzed. Expressions for the growth rates in the linear stage of the instability are obtained, and the threshold amplitudes of the external electric field above which the parametric instability can occur are found. The spectrum of the excited waves is analyzed as well. Дослiджено нерезонансне параметричне збудження зустрiчних поверхневих хвиль однорiдним у просторi та змiнним у часi електричним полем накачки, яке є перпендикулярним до планарної межi плазма-дiелектрик. Отримано та проаналiзовано критерiй збудження поверхневих хвиль. Знайдено iнкременти росту поверхневих хвиль на початковiй стадiї нестiйкостi, а також пороговi значення амплiтуди зовнiшнього поля накачки, при перевищеннi яких можливий розвиток параметричної нестiйкостi. Вивчено спектр хвиль, що збуджуються. Исследовано нерезонансное параметрическое возбуждение встречных поверхностных волн однородным в пространстве и переменным во времени электрическим полем накачки, перпендикулярным плоской границе плазма-диэлектрик. Получен и проанализирован критерий возбуждения поверхностных волн. Найдены инкре- менты роста поверхностных волн на начальной стадии неустойчивости, а также пороговые значения амплиту- ды внешнего электрического поля, выше которых возможно развитие параметрической неустойчивости. Изучен спектр возбуждаемых волн.